PERAN LEMBAGA KURSUS MENGEMUDI DALAM SOSIALISASI PERATURAN LALU LINTAS TERHADAP KEDISIPLINAN PENGEMUDI MOBIL DI PEKANBARU (STUDI KURSUS PANDU) - Andri Teguh Winata; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to (1) determine the role of institutions in the course of socializationtraffic regulations to discipline the driver's car in traffic (2) determine what form of trafficviolations committed by the driver of the car. Materials provided by the institution driving courseis divided into two, namely the material in an enclosed area and open area. To determine the roleof the researcher compared the course of understanding between participants driving courseswith drivers who do not use the services of a driving course.The results of this research found that the understanding of the driving technique amongcourse participants driving with drivers who do not use the services of the course does not have asignificant difference, or can be called both of them have almost the same understanding.But knowledge of the Law No. 22 on Traffic and Land Transportation, both on traffic signsand road markings and disciplinary problems in driving looks very striking difference is the levelof discipline driver course participants is higher than drivers who do not use the services of thecourse.keywords: Car Driver, Traffic Discipline.